2022
DOI: 10.3390/jof8020148
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Functional Characterization of a Putative Alternative Oxidase (Aox) in Sporisorium reilianum f. sp. zeae

Abstract: The mitochondrial electron transport chain consists of the classical protein complexes (I-IV) that facilitate the flow of electrons and coupled oxidative phosphorylation to produce metabolic energy. The canonical route of electron transport may diverge by the presence of alternative components to the electron transport chain. The following study comprises the bioinformatic identification and functional characterization of a putative alternative oxidase in the smut fungus Sporisorium reilianum f. sp. zeae. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 41 publications
(45 reference statements)
0
1
0
Order By: Relevance
“…Moreover, the additional alternative oxidases (AOX), which can transfer electrons from ubiquinone to O2 bypassing Complex III and IV, have been identified in the nuclear genomes of various phytopathogens, including Botrytis cinerea, Magnaporthe oryzae, Ustilago maydis, Sporisorium reilianum, and the like. And the AOX is mainly responsible for the environmental stresses in fungi [24,[26][27][28]. In terms of the ATP synthase gene, studies have found that in the mitochondrial genome of Erysiphe necator, there is a significant loss of amino acid sequences in the conserved functional domains of the N-terminal region in atp9 [29].…”
Section: The Coding Genes Of the Fungal Mitochondrial Genomementioning
confidence: 99%
“…Moreover, the additional alternative oxidases (AOX), which can transfer electrons from ubiquinone to O2 bypassing Complex III and IV, have been identified in the nuclear genomes of various phytopathogens, including Botrytis cinerea, Magnaporthe oryzae, Ustilago maydis, Sporisorium reilianum, and the like. And the AOX is mainly responsible for the environmental stresses in fungi [24,[26][27][28]. In terms of the ATP synthase gene, studies have found that in the mitochondrial genome of Erysiphe necator, there is a significant loss of amino acid sequences in the conserved functional domains of the N-terminal region in atp9 [29].…”
Section: The Coding Genes Of the Fungal Mitochondrial Genomementioning
confidence: 99%